Isolation and identification of Penicillium spp. from wheat-growing agricultural soils and their potential to promote plant growth - Visagie, Aiden Weidner (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.